2016
DOI: 10.1016/j.mulfin.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A calendar effect: Weekend overreaction (and subsequent reversal) in spot FX rates

Abstract: This paper investigates a calendar effect, namely the weekend overreaction, in spot foreign exchange markets of 8 major and 9 emerging currencies. We find that after a large price difference between Friday close and subsequent Monday open, most markets are likely to reverse in multiple horizons during the following week, which is consistent with the overreaction hypothesis. We develop a reversal trading strategy to exploit this effect which we show are robust to transaction costs and interest rates. In the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“… Parikakis and Syriopoulos (2008) also study the case of the foreign exchange market and find that the Turkish lira, the Brazilian real and the US dollar overreact, while the British pound underreacts. Dao et al (2016) confirm that the overreaction hypothesis is validated for spot foreign exchange markets. Indeed, after a large price difference between Friday close and subsequent Monday open, most markets are likely to reverse in multiple horizons during the following week.…”
Section: Review Of the Literaturesupporting
confidence: 76%
“… Parikakis and Syriopoulos (2008) also study the case of the foreign exchange market and find that the Turkish lira, the Brazilian real and the US dollar overreact, while the British pound underreacts. Dao et al (2016) confirm that the overreaction hypothesis is validated for spot foreign exchange markets. Indeed, after a large price difference between Friday close and subsequent Monday open, most markets are likely to reverse in multiple horizons during the following week.…”
Section: Review Of the Literaturesupporting
confidence: 76%
“…Further investigation by French (1980) showed that returns on Mondays usually are negative. After this influencing paper, hundreds of similar papers appeared searching for the dayof-the-week effect in different financial markets and assets: 19 developed stock markets all over the world (Agrawal & Tandon, 1994), emerging stock markets (Caporale et al, 2016), commodity markets (Singal and Tayal, 2014), FOREX (Dao et al, 2016) and cryptocurrency market etc. Plastun et al (2019) show that the "golden age" of day-of-the-week effect was in the 70-80-s of the XX th century and currently it has almost disappeared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mamede and Fernandes (2017) identified a lower return on Mondays rather than the other days of the week associated to daily returns of 2162 Brazilian Hedge Funds that did not have redemption restrictions while Dao, McGroarty and Urquhart (2016) were able to show a weekend overreaction in spot FX rates of 7 major rates and 9 emerging currency pairs with reversals in multiple horizons during the week after large weekend gaps. The weekend affect was also found in the cryptocurrency market.…”
Section: Introductionmentioning
confidence: 99%